2021
DOI: 10.1519/ssc.0000000000000680
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Conditioning Program Design Considerations for Law Enforcement Officers

Abstract: Many essential occupational tasks performed by law enforcement officers are physically demanding. There are numerous challenges with developing and maintaining physical fitness within this population. These challenges can lead to a steady decline in health and fitness over the occupational life span and have a devastating impact on officer safety and wellness. The purpose of this column is to discuss physical training program considerations when working with law enforcement professionals and provide potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 33 publications
(64 reference statements)
0
29
1
Order By: Relevance
“…Conversely, in another study by Dawes et al (9), no difference in push-up performance was observed among 20- to 29-year-old police officers (46.47 ± 14.62 repetitions) and 50- to 59-year-old officers (43.71 ± 15.09 repetitions). Of note, all of these studies (9,14,21,29) were cross-sectional studies and compared cohorts either at different times in their careers (i.e., recruits versus officers) or cohorts of different ages. None of the studies investigated longitudinal changes in physical fitness within these populations.…”
Section: Introductionmentioning
confidence: 76%
“…Conversely, in another study by Dawes et al (9), no difference in push-up performance was observed among 20- to 29-year-old police officers (46.47 ± 14.62 repetitions) and 50- to 59-year-old officers (43.71 ± 15.09 repetitions). Of note, all of these studies (9,14,21,29) were cross-sectional studies and compared cohorts either at different times in their careers (i.e., recruits versus officers) or cohorts of different ages. None of the studies investigated longitudinal changes in physical fitness within these populations.…”
Section: Introductionmentioning
confidence: 76%
“…The current body of literature suggests that academy training may not adequately prepare officers for occupational demands (Dawes et al, 2021). Moreover, cadets and officers may not understand what training is required to encourage optimal health and performance-related physical fitness.…”
Section: Resultsmentioning
confidence: 99%
“…Sit-up Test. Muscular endurance of the abdominal muscles was measured with the sit-up test, where police officers had to complete as many repetitions as possible in 1 minute (8)(9)(10)19). All police officers were required to begin the test lying in a supine position a mat, with the flexed knees forming an angle less than 90°and feet flat on the ground with the heels together.…”
Section: Methodsmentioning
confidence: 99%